2018
DOI: 10.1186/s13068-018-1051-x
|View full text |Cite
|
Sign up to set email alerts
|

Creating a more robust 5-hydroxymethylfurfural oxidase by combining computational predictions with a novel effective library design

Abstract: BackgroundHMF oxidase (HMFO) from Methylovorus sp. is a recently characterized flavoprotein oxidase. HMFO is a remarkable enzyme as it is able to oxidize 5-hydroxymethylfurfural (HMF) into 2,5-furandicarboxylic acid (FDCA): a catalytic cascade of three oxidation steps. Because HMF can be formed from fructose or other sugars and FDCA is a polymer building block, this enzyme has gained interest as an industrially relevant biocatalyst.ResultsTo increase the robustness of HMFO, a requirement for biotechnological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 32 publications
0
54
0
Order By: Relevance
“…We previously created a combinatorial library of wild‐type and mutant residues by golden gate shuffling using synthetic genes (Martin et al, ). To explore a method that avoids DNA synthesis, we now applied a PCR‐ and Gibson assembly‐based method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously created a combinatorial library of wild‐type and mutant residues by golden gate shuffling using synthetic genes (Martin et al, ). To explore a method that avoids DNA synthesis, we now applied a PCR‐ and Gibson assembly‐based method.…”
Section: Resultsmentioning
confidence: 99%
“…After an in silico screening step supported by molecular dynamics simulations, selected mutants are expressed and tested for improved stability, and successful hits are combined to a final stabilized mutant. So far, we applied the FRESCO procedure to five enzymes, and achieved considerable improvements, with T m increases up to 35°C (Arabnejad et al, ; Floor et al, ; Martin, Ovalle Maqueo, Wijma, & Fraaije, ; Wijma et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…(EC 1.1.3.13), glucose oxidase form Aspergillus niger (EC 1.1.3.4), and choline oxidase wild-type and an engineered choline oxidase variant (AcCO6) from Arthrobacter chlorophenolicus. [16,17,[22][23][24] Except for (AcCO6), all these oxidases did not convert 4 same reaction conditions as with AOX*. Furthermore, AcCO6 was found to suffer from severe substrate inhibition.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…This FAD-containing biocatalyst can oxidize 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid in three consecutive oxidations. [16,17] Another recent demonstration of the biocatalytic potential of a flavoprotein alcohol oxidase was recently reported by Turner and co-workers. They showed that choline oxidase can be engineered towards a wider substrate acceptance, for the selective oxidation of primary alcohols to aldehydes.…”
mentioning
confidence: 95%
“…Recently, however, alcohol oxidases have begun to attract more attention. A fungal alcohol oxidase was engineered towards activity with glycerol, and 5‐hydroxymethylfurfural oxidase (HMF oxidase) has been engineered for enhanced catalytic activity, improved overoxidation to the acid, thermostability and activity (albeit low) towards a secondary alcohol …”
Section: Introductionmentioning
confidence: 99%